Jesse Stuart On Education - LeMaster, J. R., 1934- (Book collections on Project MUSE., 1992)
Could a man who never earned a master's degree tell the nation's teachers and administrators how to run their schools? Jesse Stuart, who had a life-long love of education, did just that. From Stuart's autobiographical works, J.R. LeMaster has chosen selections that demonstrate his philosophy of learning and teaching, and his philosophy of life. The selections establish a loose chronology of events in Stuart's lifelong education and describe his experience as preschooler, student, teacher, and school administrator. This multiple perspective, LeMaster suggests, is essential to understanding the pr.